Assessing the impact of musical proficiency on percussion note identification skills in undergraduate medical students: an analysis using the Montreal Battery of Evaluation of Amusia - Jasneep Singh Chopra; Ruchi Tyagi; Saravanan Sampoornam Pape Reddy (BMC Medical Education)
Abstract Background The art of percussion in physical examination is a critical skill for clinicians, offering insights into the condition of internal organs. Historical ties between music and medicine, exemplified by Apollo, the Greek God of both domains, suggest a potential correlation between musical aptitude and clinical acumen. This study investigates the relationship between musical abilities, as measured by the Montreal Battery of Evaluation of Amusia (MBEA), and the proficiency in identifying percussion notes among medical students. Methods A cross-sectional study was conducted with 250 pre-clinical undergraduate medical students from the state of Uttar Pradesh, India. Participants completed the MBEA, which assesses various aspects of music processing, along with a self-engineered percussion sound test. The percussion test involved identifying different percussion notes from clinical demonstration videos. Correlation and regression analyses were performed to evaluate relationships between MBEA scores, prior musical training, and proficiency in identifying percussion notes. Statistical significance was determined at p < 0.05. Results Among 250 participants, 38.8% had prior musical experience. MBEA scores weakly correlated with percussion competency (r≈0.18, R^2 = 0.033, p = 0.003), while prior training in music strongly correlated with MBEA scores (r≈0.89, p < 0.001) and modestly with percussion competency (r≈0.23, p < 0.001). Logistic regression revealed variability in predictive accuracy, highlighting the complex interplay of factors influencing auditory skills and supporting music education as a supplementary tool in medical training. Conclusion The study indicates a minimal correlation between musical aptitude and the ability to discern percussion notes, highlighting the complexity of auditory perception skills among medical students. While prior musical experience shows a stronger association with MBEA scores, the overall impact on clinical percussion skills appears limited. These findings suggest that while there may be a relationship between musical training and auditory skills, it is not a strong predictor of clinical percussion proficiency.